Bond Strength Comparison of Orthodontic Bonding Systems: A Systematic Review (Bangladesh Journal of Orthodontics and Dentofacial Orthopedics, 2019)
As a means of regular practice in orthodontics and aesthetic dentistry, resin based adhesive systems are being used exclusively. Keeping up with the ever-increasing demand for aesthetic dental treatment all over the world, newer and more improved adhesive systems have been developed. However, regarding the comparison as to which bonding system performs better in clinical perspective, there is lack of existing scientific review articles. In this review, we tend to explore the conventional etch and rinse bonding system and the self-etch primer bonding system. The different tests to assess and compare bond strength between these two types of adhesives from various bibliography are discussed. The results of shear bond strength test, adhesive remnant index (ARI), enamel-adhesive interface using scanning electron microscope (SEM) and the effect of saliva contamination and time are discussed. Interestingly, each system has its strengths and weaknesses. In shear bond strength, self-etch bonding systems clearly exhibits less strength than conventional bonding systems. Resin tags into enamel surface are shorter in self-etch primer adhesives which results from milder etching to enamel compared to the conventional aid-etch and rinse adhesives. Contrarily, the irreversible changes to enamel surface is more aggressive in conventional acid-etching which states that self-etching systems are better according to the principles of minimal intervention dentistry.Ban J Orthod & Dentofac Orthop, April 2017; Vol-7 (1-2), P.20-26